Library System Using Radio Frequency Identification (RFID) and Telegram Bot API - Arimbawa P, Dewa Agung Krishna; Gede Darma Putra, I Ketut; Sukarsa, I Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 1 April 2018, 2018)
Libraries as a service provider to the user that needs fast, easy, and efficient services. Optimization of the services performed by the application of information technology such as utilizing barcode technology for the library system. Along with the development, there were some shortcomings in the use of barcode technology. Barcode technology can be replaced by RFID (Radio Frequency Identification) in order to further improve the operational and library services. RFID has some advantages over the barcode system is the possibility of data can be read automatically without regard to alignment readings, past the non conductor materials like cardboard paper with access speeds of several hundred tags per second at a distance of several meters. The advantages and capabilities of RFID can be applied in a library system in the inventory, self-service, and security so as to generate optimal library services more than manual systems or even a barcode system. Utilization of RFID technology in the library and then combined with technology Telegram Bot API as a medium to facilitate user access such as notification, accessing history, and others.